EFEKTIFITAS BANNER ADS DIBANDINGKAN MEDIA IKLAN KONVENSIONAL - SAGITA, ERWIN (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Advertising by using Internet media have a lot of different marketing strategies Further strategy uses banner ads which is one of the strategies of marketing via the internet's most widely used in addition to the email campaign. Shape, size, content and placement of a banner ads must be observed in order to be considered by the visitors of the website. The paperhas been focuses on idenfyedby the advantages, benefits and application of banner ads on the internet as a medium of advertising.Banner advertising is a tool for customer retention, such as banner ads is the builder of relationships and have a positive effect on the probability of purchase. Here are five important things that we need to pay attention so that ourbannerads more effective. (1) a mature draft; (2) know the target market that is more clear and precise; (3) Learn the bannerads before; (4) make the Offer attractive and clear; (5) the banner ads is created not for throwing money away